Feasibility of radar-based detection of floating macroplastics at microwave frequencies - Felício, J. M.; Costa, T. So Da; Vala, M.; Leonor, N.; Costa, J. R.; Marques, P.; Moreira, A. A.; Caldeirinha, R. F. S.; Matos, S.; Fernandes, C. A.; Fonseca, N. J. G.; de Maagt, P. (IEEE Transactions on Antennas and Propagation, 2024)
Plastic marine litter is becoming a major environmental concern. Microwaves (MW) have potential for remote detection of floating macroplastics operating from Satellites or Airborne platforms, but very scarce and limited studies exist in the literature evaluating MW radar effectiveness for this purpose. We present first results of a systematic study on MW scattering of floating low-mass macroplastics at 2-20 GHz frequency band using radar techniques. Data was first collected in small-scale measurement campaigns carried out in an indoor facility capable of producing deep sea-like wave patterns, with different floating single-use plastic items. The study reveals that, for these targets, one important scattering contribution arises from the indentation they produce on the water. For the tested conditions, targets, and metrics, it was possible to detect several types of floating plastic targets down to 10 g/m 2 concentration. Detection tended to significantly improve at the X-band, although the detection threshold depends on the combination of the mentioned conditions. Tests were extended also to two small-scale outdoor scenarios with natural wind and capillary waves. Detection of macroplastics was successful in these tested scenarios.